Pengaruh Spiritual Leadership Terhadap Kinerja Sdm Dengan Workplace Spirituality Sebagai Variabel Intervening - Khafid, Abdul; Astuti, Arum Puji; Fauzi, Muhammad (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2024)
Abstract This research aims to determine the influence of spiritual leadership on performance with work place spirituality as an intervening variable. This research uses a quantitative approach method with the Smart-PLS test tool. The population in this study were all employees of PT. Sun Life Financial Sharia Insurance AL FATEEH Semarang Branch has 204 employees, with a sample size of 102 employees. The research results show that spiritual leadership has a positive and significant influence on HR performance. Work place spirituality has a positive and significant effect on HR performance and work place spirituality has a positive role and influence in mediating the influence of spiritual leadership on performance Keywords: Spiritual Leadership, Work place spirituality, Human Resources performance Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh Spiritual leadership terhadap kinerja dengan Work place spirituality sebagai variabel intervening. Penelitian ini menggunakan metode pendekatan kuantitatif dengan alat uji Smart-PLS. Populasi dalam penelitian ini adalah seluruh karyawan PT. Asuransi Syariah Sun Life Financial Cabang AL FATEEH Semarang berjumlah 204 karyawan, dengan jumlah sampel sebanyak 102 karyawan. Hasil penelitian diketahui bahwa Spiritual leadership memiliki pengaruh positif dan signifikan terhadap kinerja SDM. Work place spirituality berpengaruh positif dan signifikan terhadap kinerja SDM . Work place spirituality memilki peran dan pengaruh positif dalam memediasi pengaruh Spiritual leadership terhadap Kinerja. Kata Kunci: Spiritual Leadership, Work place spirituality, Kinerja SDM